ANALYSIS OF FINANCIAL PERFORMANCE PRE AND POST INITIAL PUBLIC OFFERING (IPO) AT BANK CENTRAL ASIA TBK. - Wetik, Wilhelm A. A. (FEB Universitas Sam Ratulangi Manado, 2013)
Several banks took a policy to go public or initiate initial public offering policy (IPO) in order to gain access to capital. This capital surplus is very useful for banks expansion to increase their performance and support their operation and lower the risk of going bankrupt. In its process, banks must prepare prospectus to fulfil the requirement before going public. Prospectus contains accounting information and non-accounting information from companies who want to go public. These kinds of information are very useful to analyze the soundness of the bank and help bank to gain new investors and public confidence. The objective of this research is to compare pre and post of IPO at Bank Central Asia Tbk. by analyzing financial performance ratios through CAMEL ratios. Theories supporting this research are financial management and financial statement. The population is financial data with sample of data is year 1998 to 2002 with May, 2000 as IPO year. This research uses two years before IPO and two years after IPO and is analyzed with paired sample analysis. Result and conclusion are there is a significant difference of company financial performance pre and post IPO and that IPO of Bank Central Asia, Tbk. gives a significant difference on company financial performance. Keywords: financial performance, pre ipo, post ipo, financial ratio, paired sample analysis